The Importance of Work Environment and Knowledge Management in Improving Employee Performance - Yuli Nunul Mirawati; Nurul Qomariah; Abadi Sanosra (International Journal of Management Science and Information Technology, 2024)
In the face of increasing competition, companies or organizations are obliged to improve employee performance. It is very important to do this to maintain the existing conditions. This research aims to examine the influence of the work environment and knowledge management on the performance of District Communication and Information Service employees. All employees of the Jember Regency Communication and Information Service were used as the population, the number of which was 129 respondents, all of whom were used as research samples (saturated samples). Analysis of respondents in the form of descriptive analysis was carried out in this research. The measuring instrument will be tested with research validity and reliability. To answer the hypothesis in this research, a research hypothesis test was carried out. After statistical analysis was carried out, the research results showed that the work environment in which employees worked influenced employee performance. The management knowledge possessed by employees at the District Communication and Information Service also apparently has a positive impact on improving employee performance.